Adaptations to high-intensity training are independent of gender - Astorino, T. A.; Allen, R. P.; Roberson, D. W.; Jurancich, M.; Lewis, R.; McCarthy, K.; Trost, E. (European Journal of Applied Physiology, 2011)
The purpose of this study was to identify potential gender discrepancies in adaptation to low-volume high-intensity interval training (HIT). Active, young men (n = 11, age = 25.3 ± 5.5 years) and women (n = 9, age = 25.2 ± 3.1 years) matched for age, physical activity, and VO2max completed six sessions of HIT separated by 48 h over a 2-3 week period. Subjects completed four Wingate tests on days 1 and 2, five on days 3 and 4, and six on days 5 and 6. A control group of five men and four women (age = 22.8 ± 2.8 years) completed all testing, but did not perform HIT. Changes in VO2max, oxygen (O2) pulse, peak/mean power output, fatiguability, substrate oxidation, and voluntary force production of the knee flexors and extensors were examined pre- and post-training with repeated measures ANOVA, with gender and group as between-subjects variables. Results showed significant (p < 0.05) improvements in VCO2max and peak/mean power output in response to HIT, as well as reduced respiratory exchange ratio and heart rate during submaximal exercise. The magnitude of change in VO2max (5.9 vs. 6.8%), power output (10.4-14.9% vs. 9.1-10.9%), and substrate oxidation was similar (p > 0.05) between men and women. Data show that adaptations to 6 days of low-volume HIT are similar in men and women matched for VO2max and physical activity.